Association of red cell distribution width in diagnosis and severity of iron deficiency anaemia - Panthi, Prabha; Maharjan, Sushna; Dhakal, Nirbija; Koirala, Subash; Thapa, Roshna (Journal of Chitwan Medical College, 2025)
Introduction: Iron deficiency anaemia (IDA) is the most prevalent micronutrient deficiency in the world. Detection of IDA largely depends upon quantification of biochemical markers like serum ferritin, transferrin saturation, which are not routinely available and affordable in developing countries. Our study aims to show relationship between red cell distribution width (RDW) and the severity of IDA. Method: A cross-sectional study was conducted at Chitwan Medical College from 01 Jun 2022 to 31 May 2023 on patients who presented with microcytic anaemia after receiving ethical clearance from the Institutional Review Committee. Patients with a recent history of iron therapy, blood transfusion or leucocytosis were excluded from the study. Patients’ information was retrieved from the Medical Information Data Analysis System software, and IBM SPSS Statistics 20 was used to evaluate the results. The receiver operating characteristic curve was used to assess the efficiency of RDW in diagnosing IDA. Result: In total, 204 cases were studied and found a significant association between age group and IDA status (Ӽ2=9.55, p=0.008). Receiver’s operating characteristic curve found at a cut-off of 14.5% RDW, sensitivity was 97% and specificity 27% and at a cut-off of 21%, sensitivity was 17% and specificity 90%, indicating that with increased value of RDW, the extent of specificity for diagnosis of IDA also increases. Conclusion: The RDW can be a useful tool to be evaluated in conjunction with other clinical and laboratory results to increase diagnostic accuracy, but it is not a reliable diagnostic tool for IDA on its own.